Between God and the Sultan a history of Islamic law - Vikor, Knut S. (Oxford University Press, 2005)
Knut S. Vikor introduces the development and practice of Islamic law to a wide readership: students, lawyers, and the growing number of those interested in Islamic civilization. He summarizes the main concepts of Islamic jurisprudence; discusses debates concerning the historicity of Islamic sources of dogma and the dating of early Islamic law; describes the classic practice of the law, in the formulation and elaboration of legal rules and practice in the courts; and sets out various substantive legal rules, on such vital matters as the family and economic activity.